Factors that contribute to public sector nurses' turnover in Limpopo province of South Africa - Takalani G. Tshitangano (AOSIS, 2013)
Background: The ongoing worldwide phenomenon of a shortage of about 4.3 million nurses and midwives poses a threat to health service delivery. Limpopo province had the worst nurse shortage of over 60% in 2010. Authors attribute this shortage to turnover of nurses. The quest to describe factors contributing to nurses' turnover led to this study in Limpopo province,South Africa. Objectives: To explore and describe factors that contribute to nurses' turnover in Limpopo province of South Africa by assessing public sector nurses' job satisfaction in relation to common determinants of job satisfaction. Method: A descriptive cross-sectional approach used primary quantitative data collected from 141 of 380 respondents (31.1% response rate) contacted incidentally. Self-administered hand delivered questionnaires were used to gather ordinal data, which were analysed in terms off requency and percentage tables using the Statistical Package for Social Sciences version 6. The sum of positive and negative effects was used to determine satisfaction; if positive effects were greater than negative effects respondents were judged to be satisfied and vice versa. Results: Frequency and percentage tables revealed that nurses in Limpopo province were more dissatisfied (53.9%) than satisfied (37.8%) with their jobs. Factors which respondents were found to be dissatisfied with included staffing (85.2%), availability of workplace resources(83.7%), salaries (78.8%), workplace safety (73.7%), career development opportunities (64.5%) and hours of work (47.6%). Conclusion: Nurses' turnover is attributed to nurses' dissatisfaction with staffing, resources, salaries and workplace safety. Attention needs to be given to these specific issues if retentionof nurses is to be achieved.